2010
DOI: 10.1016/j.rbmo.2010.05.002
|View full text |Cite
|
Sign up to set email alerts
|

Chromosome abnormality rates in human embryos obtained from in-vitro maturation and IVF treatment cycles

Abstract: The aim of this retrospective study was to compare the incidence of chromosomal abnormality in embryos from in-vitro maturation (IVM) and IVF cycles. The copy numbers of chromosomes 13, 15, 16, 18, 21, 22, X and Y were assessed with fluorescence in-situ hybridization (FISH) in single blastomeres biopsied from cleavage stage embryos. Spare embryos that were not transferred or cryopreserved were also analysed in full. IVM and IVF groups comprised six and 30 couples, with mean ± SD embryos with FISH result of 8.0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
31
0
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 66 publications
(35 citation statements)
references
References 24 publications
2
31
0
2
Order By: Relevance
“…IVM timing was also a factor with respect to the induction of chromosome aneuploidy of IVM embryos. Zhang et al studied the chromosome abnormality rates in human embryos obtained from in vitro maturation and IVF treatment cycles, and they found that the aneuploidy will be significantly increased in embryos derived from oocytes that matured 48 h after collection compared with oocytes matured 24 h or the control group [50]. Emery et al also reported that the incidence of aneuploidy in embryos with delayed fertilization for IVM oocytes would reach approximately 80%, which was significantly higher than in the control group [51].…”
Section: Discussionmentioning
confidence: 99%
“…IVM timing was also a factor with respect to the induction of chromosome aneuploidy of IVM embryos. Zhang et al studied the chromosome abnormality rates in human embryos obtained from in vitro maturation and IVF treatment cycles, and they found that the aneuploidy will be significantly increased in embryos derived from oocytes that matured 48 h after collection compared with oocytes matured 24 h or the control group [50]. Emery et al also reported that the incidence of aneuploidy in embryos with delayed fertilization for IVM oocytes would reach approximately 80%, which was significantly higher than in the control group [51].…”
Section: Discussionmentioning
confidence: 99%
“…The clinical and embryology laboratory IVM protocols exercised in our unit are described in elsewhere [10,11]. Briefly all women underwent a transvaginal ultrasound scan on the 2 nd or 3 rd day of a spontaneous or progestin induced menstrual bleeding to exclude ovarian cysts and endometrial pathology.…”
Section: Ivm Protocolmentioning
confidence: 99%
“…In Vitro Maturation (IVM) treatment involves collection of oocytes relatively earlier in the follicular phase when the majority is expected to be still immature and therefore does not require Controlled Ovarian Hyperstimulation (COS) [10,11]. Different follicular dynamics, the shorter duration of proliferative phase and the lack of exposure of endometrium to supraphysiological estrogen levels can lead to a different endometrial environment in IVM cycles than in conventional COS -IVF cycles.…”
Section: Introductionmentioning
confidence: 99%
“…Embryos frozen on day 2 were cultured for an additional day after thawing before the blastomere biopsy was performed as described previously [19,20]. Embryos frozen on day 3 were thawed in the morning and biopsied on the same day after culturing for a few hours for equilibration.…”
Section: Vitrification and Warming Proceduresmentioning
confidence: 99%